2020
DOI: 10.1051/e3sconf/202021403029
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Cultural Added Value Research Based on Knowledge Mapping Analysis

Abstract: The enhancement of cultural added value to products is reflected in the level of personal cultural spiritual enjoyment, corporate cultural brand building and social cultural essence inheritance. Compared with ordinary products, the added value of products after incorporating cultural elements is the size of the product’s cultural added value. At the same time, different components of cultural added value can meet different cultural needs of consumers and reach emotional consensus with consumers to some extent.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Designers can use specific cultural characteristics to enhance the value of products, which helps promote social and economic development and push the region's unique culture to the international market. Past studies have shown that innovative products with cul-tural value can shape consumers' cultural concepts and make products become cultural communicators, which is also conducive to connecting traditional culture with modern life (Gu et al, 2022;Yuan et al, 2020;Qin & Ng, 2020;Qin et al, 2019). Artistic and creative products give consumers a deeper understanding of conventional culture and regional characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Designers can use specific cultural characteristics to enhance the value of products, which helps promote social and economic development and push the region's unique culture to the international market. Past studies have shown that innovative products with cul-tural value can shape consumers' cultural concepts and make products become cultural communicators, which is also conducive to connecting traditional culture with modern life (Gu et al, 2022;Yuan et al, 2020;Qin & Ng, 2020;Qin et al, 2019). Artistic and creative products give consumers a deeper understanding of conventional culture and regional characteristics.…”
Section: Introductionmentioning
confidence: 99%